Become Amphibians - Calandrón, Sabrina (Universidad Nacional del Litoral, 2019)
This article studies the recent transformations of the activities, areas of action and responsibilities of the Prefectura Naval Argentina. The analysis is oriented to security policies of “saturation” in large urban centers, from the 2000s to the 2015. This produced different phenomena in the Prefecture that are addressed in this work: 1) the preparation, training and organization of a personnel for security tasks; 2) the modification of expectations of professional careers, valuation of transfers and meanings of informal punishment; 3) reaffirmation of prefectural identification with water and navigation; 4) proliferation of judicial conflicts due to the actions in the staff. The focus of this work is the conceptions and explanations of the structural changes and the new intervention tools of the members of the Prefectura Naval Argentina. As a result, we find a tension between the ideas of modernization of the security forces, on the one hand, and the idea of disintegrating security objectives, on the other hand.